Inner amenable hypergroups, invariant projections and Hahn-Banach extension theorem related to hypergroups - TAHMASEBI, Nazanin (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
Let K be a hypergroup with a Haar measure. In the present paper we initiate the study of inner amenable hypergroups extending amenable hy pergroups and inner amenable locally compact groups. We also provide charac terizations of amenable hypergroups by hypergroups having the Hahn-Banach extension or monotone projection property. Finally we focus on weak*-invariant complemented subspaces of L1(K). Mathematics Subject Classification (2010): 43A07.